2019
DOI: 10.1002/gps.5132
|View full text |Cite
|
Sign up to set email alerts
|

Development of memory clinics in the Netherlands over the last 20 years

Abstract: Objectives Memory clinics (MCs) have been established to improve diagnosis and treatment of cognitive disorders, including dementia. The aim of this study was to determine the characteristics and working methods of MCs in the Netherlands in 2016. More insight into different working methods can be used to improve the quality of care in Dutch MCs. Additionally, the findings will be compared with earlier results to investigate the development of MCs since 1998. Methods A survey was sent in 1998, 2004, 2009, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 40 publications
0
58
0
Order By: Relevance
“…MRI, blood tests, and NPA). Previous research showed that providing the patient and family with extensive feedback on the neuropsychological findings was not a universal service in Dutch MCs (Gruters et al, 2019). However, providing patients with feedback on their cognitive performance was shown to lead to improved quality of life and social adjustment (Rosado et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MRI, blood tests, and NPA). Previous research showed that providing the patient and family with extensive feedback on the neuropsychological findings was not a universal service in Dutch MCs (Gruters et al, 2019). However, providing patients with feedback on their cognitive performance was shown to lead to improved quality of life and social adjustment (Rosado et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the Dutch healthcare system, it is mandatory to be referred by a doctor for it to be covered by the insurance companies. The proportion of patients who remained in care of Dutch MCs varied between 10% and 100% (Gruters et al, 2019). However, most clinics do not offer a second consultation shortly after the diagnostic disclosure, which might be related to financial barriers or procedures within the clinics themselves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations